Playing to prepare for adulthood : the games of Kanome children - Sri Murni (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research focuses on Kanome children’s traditional games aims to answer several questions: what are the traditional children’s games in Kanome? What are the functions of the traditional games for the lives of the children? Why are the traditional games played today? This study aims to identify and document the types of games, the functions and the cultural values embodied in the Kanome traditional games. The data is taken through qualitative method by conducting in-depth interviews and observation. The research finds that games such as tai-tai, kiri mbal-bal, and mbanti have the following functions: (i) to prepare a child for adulthood (ii) as a means of recreation, (iii) as a means of media learning, (iv) to flourish the children’s creativity (developing intellectual character), (v) to teach honesty and sportsmanship; (vi) to show a friendly and mutual cooperation, (vii) to sharpen the skills of the children, (viii) to give meanings of social, environmental, and natural interactions. (ix) to enjoy kumbili harvests.